Circulating circRNA as biomarkers for dilated cardiomyopathy etiology - Costa, Marina C.; Calderon-Dominguez, Maria; Mangas, Alipio; Campuzano, Oscar; Sarquella-Brugada, Georgia; Ramos, Mónica; Quezada-Feijoo, Maribel; Pinilla, José Manuel García; Robles-Mezcua, Ainhoa; del Aguila Pacheco-Cruz, Galan; Belmonte, Thalia; Enguita, Francisco J.; et al. (Journal of molecular medicine (Berlin, Germany), 2021)
Dilated cardiomyopathy (DCM) is the third most common cause of heart failure. The multidisciplinary nature of testing — involving genetics, imaging, or cardiovascular techniques — makes its diagnosis challenging. Novel and reliable biomarkers are needed for early identification and tailored personalized management. Peripheral circular RNAs (circRNAs), a leading research topic, remain mostly unexplored in DCM. We aimed to assess whether peripheral circRNAs are expressed differentially among etiology-based DCM. The study was based on a case–control multicentric study. We enrolled 130 subjects: healthy controls ( n = 20), idiopathic DCM ( n = 30), ischemic DCM ( n = 20), and familial DCM patients which included pathogen variants of (i) LMNA gene ( n = 30) and (ii) BCL2-associated athanogene 3 ( BAG3 ) gene ( n = 30). Differentially expressed circRNAs were analyzed in plasma samples by quantitative RT-PCR and correlated to relevant systolic and diastolic parameters. The pathophysiological implications were explored through bioinformatics tools. Four circRNAs were overexpressed compared to controls: hsa_circ_0003258, hsa_circ_0051238, and hsa_circ_0051239 in LMNA -related DCM and hsa_circ_0089762 in the ischemic DCM cohort. The obtained areas under the curve confirm the discriminative capacity of circRNAs. The circRNAs correlated with some diastolic and systolic echocardiographic parameters with notable diagnostic potential in DCM. Circulating circRNAs may be helpful for the etiology-based diagnosis of DCM as a non-invasive biomarker. Key messages The limitations of cardiac diagnostic imaging and the absence of a robust biomarker reveal the need for a diagnostic tool for dilated cardiomyopathy (DCM). The circular RNA (circRNA) expression pattern is paramount for categorizing the DCM etiologies. Our peripheral circRNAs fingerprint discriminates between various among etiology-based DCM and correlates with some echocardiographic parameters. We provide a potential non-invasive biomarker for the etiology-based diagnosis of LMNA-related DCM and ischemic DCM.